Effect of Cocos nucifera and Jatropha gossypiifolia oils on the asphaltenes stability - Marín Velásquez, T.D.; Arriojas Tocuyo, D.D.J. (Nexo Revista Científica, 2020)
The objective was to evaluate Cocos nucifera and Jatropha gossypiifolia oils as asphaltene stabilizers in a medium crude oil from Campo El Furrial Estado Monagas, Venezuela. Two samples were used for each oil, one of which was heated to 140 °C for 24 hours. Three mixtures were prepared for each diesel oil (30, 40, and 50%). Eight μl were applied from each mixture to 10 ml of petroleum and the flocculation threshold (UF) of asphaltenes was obtained as the ml of n-heptane applied to observe aggregates in an optical microscope and the dispersion point (PD) as the ml of xylene to solubilize the asphaltene aggregates formed. The Instability Index (INE) represents the relationship between UF and PD. The experimental design was factorial with a response variable (INE) and 3 experimental factors (Type of Oil, Temperature and Percentage of Oil). The package Statgraphics Centurion XVII was used with α = 0.05. Experimental factors and their relationships significantly influence the stability of asphaltenes in the oil used. Both oils stabilize the asphaltenes, their performance being better when heated to 140 °C and that of J. gossypiifolia was the most efficient with 71.89%.